2019
DOI: 10.1167/iovs.19-26972
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Evoked Potentials Are Reduced Compared to Axon Numbers in Rhodopsin P347L Transgenic Rabbits With Severe Photoreceptor Degeneration

Abstract: PURPOSE. To determine the relationship between the amplitudes of the electrically evoked potentials (EEPs) and the number of optic nerve axons at a late stage of retinal degeneration in rhodopsin P347L transgenic (Tg) rabbits, a model of retinitis pigmentosa. METHODS. Six eyes of six wild-type (WT) (43.8 6 7.5 months of age) and six eyes of six Tg (40.3 6 2.6 months of age) rabbits were studied. The EEPs were elicited by 1 to 5 mA of transcorneal electrical stimulation. The first positive wave, the P1 componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, most of these rabbit models were induced experimentally, which limited their application in hereditary eye diseases. Due to the lack of a technology to generate targeted gene modifications in rabbits, for many years, genetically modified rabbit models for ocular disease studies were restricted to transgenic rabbits only (Kondo et al, 2009;Yokoyama et al, 2010;Hirota et al, 2012;Ueno et al, 2013Ueno et al, , 2019Asakawa et al, 2015Asakawa et al, , 2016Nagai et al, 2016;Nakagami et al, 2016;Kominami et al, 2017Kominami et al, , 2019Okado et al, 2017;Roy et al, 2019).…”
Section: Gene Edited Rabbits For Translational Studies Of Ocular Diseasesmentioning
confidence: 99%
“…However, most of these rabbit models were induced experimentally, which limited their application in hereditary eye diseases. Due to the lack of a technology to generate targeted gene modifications in rabbits, for many years, genetically modified rabbit models for ocular disease studies were restricted to transgenic rabbits only (Kondo et al, 2009;Yokoyama et al, 2010;Hirota et al, 2012;Ueno et al, 2013Ueno et al, , 2019Asakawa et al, 2015Asakawa et al, , 2016Nagai et al, 2016;Nakagami et al, 2016;Kominami et al, 2017Kominami et al, , 2019Okado et al, 2017;Roy et al, 2019).…”
Section: Gene Edited Rabbits For Translational Studies Of Ocular Diseasesmentioning
confidence: 99%
“…Rabbits, compared with mice, are closer to humans in terms of phylogenesis, anatomical features, physiology, and pathophysiological responses [10][11][12][13][14] , and are used as a classic lab animal species to develop novel therapeutics for humans and refine medical and surgical equipment 13,[15][16][17][18][19] . Historically, retinal degeneration has been studied in rhodopsin Pro347Leu transgenic rabbits, a model of RP [20][21][22][23][24][25][26][27][28][29][30][31] . Recently, the emerging gene editing technology in rabbits has greatly increased their value to biomedicine, motivating our efforts to develop rabbits that carry the disease causing mutations found in human patients, as models to replicate human diseases more precisely [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Various noninvasive methods have been studied for eye stimulation methods. tACS (transcranial alternating current stimulation) [ 5 ], which places electrodes on the skin, TES (transcorneal electrical stimulation) [ 6 ], which places contact-lens-shaped electrodes on the cornea of the eye, and TpES (transpalpebral electrical stimulation) [ 7 , 8 ], which places electrodes on the eyelids, have been reported. It has also been suggested that stimulating the eyeball may lead to the treatment of retinitis pigmentosa and optic neuropathy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%